PENGARUH PERENCANAAN PAJAK DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Sihombing, Talenta Br.; Siregar, Retnawati; Sembayang, Minda Muliana Br (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This research was conducted to determine the effect of tax planning and company size on earnings management in mining companies listed on the Indonesia Stock Exchange from 2020-2022. The type of researchquantitative with an associative causal approach. The population consists of 41 mining companies, with 25 companies selected using purposive sampling techniques over the period3 years with a data volume of 75. The processing technique uses analysis multiple linear regression. The research results show that partially tax planningIt significantly affects earnings management, while company size does not. significantly influences earnings management. Simultaneously, tax planning and company size significantlyinfluence earnings management.